FAKTOR-FAKTOR YANG MEMPENGARUHI PENGANGGURAN (Studi Kasus Di Kecamatan Suwawa Timur Kabupaten Bone Bolango) - Joice Machmud; Arfan Suleman (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2022)
The problem of unemployment in Indonesia has always been a challenge, especially in the regions to find a solution approach. Therefore, this study aims to see what factors affect unemployment by taking the research location in East Suwawa District, Bone Bolango Regency. This study uses a descriptive quantitative approach using secondary data sources, namely time series data for the five years 2016-2021. The equipment used in problem solving analysis is multiple linear regression involving three variables, namely Y (Unemployed), X1 (Provincial Drinking Wage) and X2 (Education Level). The results of the study concluded that the minimum wage variable (X1) had a negative and significant effect on the unemployment rate (Y) in East Suwawa District. The education level variable (X2) has a significant and positive direction on the unemployment rate (Y) in East Suwawa District. The independent variables, namely the minimum wage and education level, were able to explain the variation in the dependent variable or the unemployment rate of 5.56 percent, while the remaining 44.4 percent was explained by other variables not included in the estimate. Simultaneously the minimum wage and education level have a significant effect on unemployment in East Suwawa District. In other words, the independent variables jointly affect the unemployment rate significantly.